(untitled) (Journal of the College of Education for Women, 2019)
The Iraqi-Kuwaiti relations represent a great issue for the Arab-Arab relations. This relation is characterized by specificity for the tension since the foundation of the State of Kuwait until late. There are many factors that prevented the fulfillment of the aspiration towards the development of the relations, perhaps the most important of which is the issue of Mubarak Great Port which is a difficult issue as far as the relation between the two states is concerned. One year after Iraq put the cornerstone of the Great Faw Port. This is considered as the most important hurdle in front of constructing the relations with the neighbor Kuwait